The role of price and convenience in use of oral rehydration salts to treat child diarrhea: A cluster randomized trial in Uganda - Wagner, Zachary; Asiimwe, John Bosco; Dow, William H.; Levine, David I. (PLoS journal, 2022)
This article was published in The PLoS Medicine journal [Open access, licensed under CC BY-NC-ND 4.0] and the definite version is available at: https://doi.org/10.1371/journal.pmed.1002734 The Article's website is at: https://journals.plos.org/plosmedicine/article?id=10.1371/journal.pmed.1002734